Students’ Perceptions on Using Google Classroom Application in Learning Reading - Devi Mafiza; Sri Wiyanah (JEdu: Journal of English Education, 2022)
This research aims to identify the students’ perception of the use of Google Classroom Application in learning reading. It based on the research problem that the students still adapting to the recent online learning in this pandemic situation. Students also have not fully participated in online learning, especially in reading class. The research used a qualitative method. The population in this research was the students of Universitas PGRI Yogyakarta, and the sample was the third-semester students of the English Language Education Study Program. The number of samples was 10 students. The samples were taken by using a random sampling technique. The data were collected through interviews and analyzed by using descriptive analysis through transcribing the data, member checking, and coding the data. The result showed that students’ perceptions of the use of Google Classroom Application in learning reading during online classes in this pandemic situation were positive. They stated that online learning by using Google Classroom Application in reading class was efficient and enjoyable. They enjoyed the learning activity although they cannot interact directly with the lecturer and their classmates. Minor issues such as internet connectivity, student idleness, and a lack of direct interaction with the professor were encountered by students during the online learning process, but these issues had no impact on their ability to learn to read. It may be deduced from their comment that, despite having various issues with internet connectivity and learning motivation, they are able to enjoy the learning process and participate effectively in it.